Situation Report: Hungary, 14 October 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungary Fifth Warsaw Pact Country on Karmal's List of Possible Donors Head of State Visits Portugal to Revive Bilateral Relations Prime Minister in Vienna The Mutual Benefits of the Kadar-Kreisky Era Economic Calls for Reform in the CMEA The Hungarian Stand on the Forthcoming CMEA Summit New Housing Regulations Special Administrative System in Agriculture to Be Revived